Conceptual Analysis of Proverbs with Somatic Components in English and Uzbek Languages - Boboqulova , Nilufar (The Lingua Spectrum, 2025)
This article presents a conceptual analysis of proverbs with somatic components in English and Uzbek languages. Somatic components are lexical units related to the human body and play a significant role in the phraseological system of both languages. Since proverbs reflect the worldview, traditions, and cultural values of a nation, their somatic components can provide deep insights into the mentality and linguistic features of a particular society. The study examines the semantic structure of somatic proverbs, their national and cultural characteristics, as well as their conceptual aspects. A comparative analysis of English and Uzbek proverbs with somatic components reveals how these linguistic units function in different cultural contexts. The similarities and differences in the use of somatic units in both languages are identified, highlighting their linguistic and cultural features. The findings of this article are significant for linguistics and translation theory, providing a methodological basis for comparative studies and contributing to a better understanding of intercultural communication.